(untitled) (Acta Entomologica Serbica, 2020)
Although the cerambycid fauna of Algeria has received a great deal of attention so far, additional collecting has produced one species that was not previously recorded in northwestern Algeria. Purpuricenus desfontainii (Fabricius, 1793) is recorded for the first time in northwestern Algeria from the Msila Forest. In May 2019, 50 males and 50 females of P. desfontainii were collected by hand on the flowers and stems of milk thistle. External morphological measurements were made to find possible sexual dimorphism in P. desfontainii. Results indicated that there are significant differences between males and females in the lengths of antennae and of flagellomeres. Moreover, males and females significantly differ in total body length and width, head width, ratio of antennal length to total body length, and elytral length and width.